Bailak al-Kipchaki – medieval linguist and expert on precious stones - Derbisali А. (Journal of Oriental Studies, 2021)
It is known that in the Middle Ages, vast lands inhabited by Kipchaks were called Desht-i-Kipchak (Kipchak steppe). Kipchaks also lived in the North Caucasus and Ukraine. In the first half of the XII century, the army of the Georgian king David IV numbered about 45,000 Kipchaks. That is why some toponyms in these countries are Kipchak, and elements of Kipchak origin are also found in local languages and customs. They tried to learn the Kipchak language, get acquainted with its customs and everyday life. Kipchaks also lived in Armenia. Our ancestors helped them fight external enemies. Evidence of this is the discovery in Armenia of inscriptions in the Armenian alphabet, but in the Kypchak language. The Kipchaks were the first to resolutely oppose the Mongol invasion. Unable to resist the overwhelming enemy, they were defeated and scattered throughout the Middle and Middle East. But wherever they went, the Kipchaks did not give up and forced them to respect themselves and their loved ones. That is why some Arabic scholars who spoke with the Kipchak rulers also wrote in Kipchak. Thus, a number of Arabic-Kipchak, Kipchak-Arabic dictionaries and textbooks were born. Key words: Baylak al-Kipchaki, source, Kipchak language, Kipchak script, manuscript, medieval science.